Predictive inference under model misspecification with an application to assessing the marginal predictive content of money for output - Nii Ayi Armah; Norman R. Swanson (Rutgers University, Department of Economics, 2011)
In this chapter we discuss model selection and predictive accuracy tests in the context of parameter and model uncertainty under recursive and rolling estimation schemes. We begin by summarizing some recent theoretical findings, with particular emphasis on the construction of valid bootstrap procedures for calculating the impact of parameter estimation error. We then discuss the Corradi and Swanson (CS: 2002) test of (non)linear out-of-sample Granger causality. Thereafter, we carry out a series of Monte Carlo experiments examining the properties of the CS and a variety of other related predictive accuracy and model selection type tests. Finally, we present the results of an empirical investigation of the marginal predictive content of money for income, in the spirit of Stock and Watson (1989), Swanson (1998) and Amato and Swanson (2001).
Keywords: C22; C51; 330; block bootstrap; forecasting; recursive estimation scheme; rolling estimation scheme; model misspecification; nonlinear causality; parameter estimation error; prediction; Prognoseverfahren; Zeitreihenanalyse; Inferenzstatistik; Modellierung; Geldpolitik; Wirkungsanalyse; Gesamtwirtschaftliche Produktion; Theorie